The Macmillan enclyclopedia - Isaacs, Alan (Macmillan, 1999)
All 25,000+ entries in the Macmillan encyclopedia have been reviewed and updated, and more added to cover the greatest possible width of topics for the year 2000 - countries of the world, science and technology, space, natural history, medicine, politics, sport, people, literature, art and history.